Real-world impact of dupilumab on asthma disease burden in Japan: The CROSSROAD study - Koichi Fukunaga; Etsuko Tagaya; Masato Ishida; Yoshinori Sunaga; Ryuji Koshiba; Akihito Yokoyama (Allergology International, 2023)
Background: Dupilumab, a human monoclonal anti-interleukin (IL)-4Ra antibody blocks the shared receptor component of IL-4 and IL-13, drivers of type 2 inflammation. Dupilumab is approved for severe/refractory asthma inadequately controlled by existing therapies, but knowledge of its effect on real-world disease burden is lacking. This study investigates real-world effects of dupilumab on asthma exacerbation risk and oral corticosteroid (OCS) use in Japanese individuals with asthma. Methods: This retrospective, cohort study used a Japanese insurance claims database to identify patients who started dupilumab between 26 March 2019–31 May 2020. Patients were followed for ±365 days from dupilumab initiation. The study primarily assessed the annual incidence rate of severe asthma exacerbations occurring simultaneously with hospitalizations or OCS bursts. Secondary and exploratory endpoints assessed OCS dosage and duration, and healthcare resource utilization (HRU), respectively. Results: At dupilumab initiation (N = 215), mean age was 57.2 years, 41.9% of patients were aged ≥65 years, and 59.5% were female. Dupilumab significantly reduced the annual incidence of severe asthma exacerbations from 1.29 to 0.74 (95% confidence interval, 0.44–0.76) per patient per year. Mean OCS dosage decreased from 10.4 to 7.2 mg/day in chronic OCS users; median frequency of OCS bursts decreased from 3 to 0. Both unscheduled outpatient visits (35.8% vs 29.8%) and hospitalizations (21.9% vs 12.1%) decreased. Mean (standard deviation) duration of hospitalization also decreased from 6.7 (27.6) to 2.2 (8.1) days. Conclusions: Japanese patients with asthma who received dupilumab had reduced incidence rates of severe asthma exacerbations, OCS use, and HRU over 12 months.